American racist : the life and films of Thomas Dixon - Slide, Anthony (Book collections on Project MUSE., 2004)
"Thomas Dixon has a notorious reputation as the writer of the source material for D.W. Griffith's groundbreaking and controversial 1915 feature film The Birth of a Nation . Perhaps unfairly, Dixon has been branded an arch-conservative and a racist obsessed with what he viewed as "the Negro problem." As American Racist makes clear, however, Dixon was a complex, multitalented individual who, as well as writing some of the most popular novels of the early twentieth century, was involved in the production of some eighteen films. Dixon used the motion picture as a propaganda tool for his often outrageous views.